PERILAKU PENGGUNAAN OBAT DALAM PERSPEKTIF FARMASI SOSIAL: TINJAUAN FAKTOR SOSIAL, BUDAYA, DAN EDUKASI PASIEN - Fadilla Purba, Annisa Ratna; Nor Maliza, Fera; Oktaviani, Diah (Jurnal Farmasi Aisyah, 2025)
Medication use behavior is a critical determinant of therapeutic success and patient safety, influenced not only by pharmacological aspects but also by social, cultural, economic, and healthcare system factors. The Social Pharmacy approach views medication use as a health behavior formed through the interaction of individuals with their social environment. This review article aims to integrate the findings of various scientific articles from the past seven years related to medication use behavior from a Social Pharmacy perspective. The writing method was conducted through a literature review of review articles and relevant research that discussed social and cultural factors, health literacy, the role of pharmacists, and the influence of media on medication use. The review results indicate that low medication adherence, irrational self-medication practices, and medication errors are closely related to low health literacy, socioeconomic inequality, cultural beliefs, and health misinformation. Patient education and effective communication by pharmacists have been shown to play a crucial role in shaping rational medication use behavior. In conclusion, a Social Pharmacy approach is needed to comprehensively understand and address medication use issues. Integrating social and cultural aspects into pharmaceutical practice and health policy is expected to improve adherence, safety, and rationality of medication use in the community.